A SMART VOTING SYSTEM COMBINING FINGERPRINT AND FACIAL RECOGNITION FOR ENHANCED SECURITY - Yadu, Amitesh; Chandrakar, Omprakash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Bogus (fake) voting is still a major drawback in elections. In Aadhaar card, the government has all our data base including finger print and retina. Biometric finger print devices and web cameras are used in electronic voting machines for voter verification. We have designed a smart voting machine where the user does not need to carry his ID which contains his necessary details. The person present at the polling station need only place his/her finger in the finger print scanner and capture the facial recognition on the web camera at the polling station counter, thus allowing to obtain on-spot fingerprint and facial recognition from the voter who Works. an identity. This data is sent to the control unit for verification. The controller receives data from the reader and compares this data with already existing data stored during voter registration. If the data matches the pre-stored information of the registered fingerprint and face, the person is allowed to cast his/her vote. If not, a warning message is displayed on the LCD and a warning is given through voice, thus stopping the person from casting his/her vote. The mechanism of casting votes is done manually using a keyboard. The LCD is used to display relevant messages, warnings and upcoming results.